2021
DOI: 10.1371/journal.pone.0243953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected methionine supplementation on the performance of high production dairy cows in the tropics

Abstract: Increasing methionine availability in dairy cow diets during the first third of lactation may enhance their performance and health. The aim of this study was to determine the effect of supplementing rumen-protected methionine (Smartamine® M, SM) in a lactation diet with protein and energy levels calculated according to the literature. Seventy-six multiparous Holstein cows (39.1 ± 6.8 kg of milk/d and 65 ± 28 DIM) were assigned to 1 of 2 dietary treatments (38/treatment) according to a randomized complete block… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…Some EAAs are considered limiting for milk protein synthesis under specific dietary conditions in dairy cows, typically Met and Lys ( 17 ), and probably His. The increase in milk protein percentage and yield observed in this study in response to RPL and RPM agreed with what was previously obtained ( 9 , 14 , 16 , 61 , 62 ), but not always ( 27 , 63 , 64 ). Consistent with other studies, there was a positive response of dietary RPL and RPM supply on milk yield for transition and lactating and beef cows ( 13 , 14 , 16 , 61 , 65 , 66 ), but this response is not universal ( 12 , 27 , 67 69 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some EAAs are considered limiting for milk protein synthesis under specific dietary conditions in dairy cows, typically Met and Lys ( 17 ), and probably His. The increase in milk protein percentage and yield observed in this study in response to RPL and RPM agreed with what was previously obtained ( 9 , 14 , 16 , 61 , 62 ), but not always ( 27 , 63 , 64 ). Consistent with other studies, there was a positive response of dietary RPL and RPM supply on milk yield for transition and lactating and beef cows ( 13 , 14 , 16 , 61 , 65 , 66 ), but this response is not universal ( 12 , 27 , 67 69 ).…”
Section: Discussionsupporting
confidence: 92%
“…The lower MUN shown in this study indicates greater efficiency of N utilization. Lowered MUN has previously been observed by supplying RPAA form, including Met, Lys, leucine, threonine, and isoleucine separately or two in combination to lactating dairy cows ( 28 , 29 , 78 ), with no response in others ( 13 , 27 , 43 , 61 , 68 ). In this study, continual supplementing RPAA to transition and lactating dairy cows may improve udder health as indicated by the lowered milk SCC, as reported earlier in this study during the perinatal period ( 18 , 29 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The retrieved studies were screened according to the corresponding inclusion criteria. After excluding the duplicate and unqualified literature, the meta-analysis included 14 studies, as shown in Table 1 [ 1 , 2 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. To make it easier to visualize the studied datasets, the mean, maximum, minimum, and standard deviation of each study parameter are summarized in Table A1 of Appendix A .…”
Section: Resultsmentioning
confidence: 99%
“…Met is the first limiting AA for ruminants [17]. Increasing the Met supply by feeding diets supplemented with RPM can increase the milk yield and MP yield [37,38,42,50]. The resistance to rumen degradation of many Met analogs have been studied.…”
Section: Metmentioning
confidence: 99%